Improving the Quality of Gembili Pickle (Dioscorea esculenta) Through Fermentation with Starter Culture Lactobacillus plantarum B1765 - Nugrainglahi, Yurita Gita Puspa; Wikandari, Prima Retno (Jurnal Pijar Mipa, 2025)
Gembili is a type of tuber that grows widely in Indonesia and has the potential to be developed into functional food, but its utilization has not been optimal. One of the efforts that can be made is the development of gembili as pickle, a synbiotic fermented product of gembili by a starter culture of Lactobacillus plantarum B1765, which has been known as a probiotic. This study examines the effect of fermentation duration on the growth of total lactic acid bacteria (LAB), pH value, Total Titratable Acidity (TTA), and organoleptic quality aspects.  The gembili tubers were cut into sticks and fermented for 0, 2, 4, and 6 days, using Lactobacillus plantarum B1765 starter culture at 37℃. Total LAB was calculated by total plate count (TPC), pH by pH meter, TTA by acid-base titration, and organoleptic test using untrained panellists to assess the preference level using a hedonic scale. The results showed that total LAB increased from the beginning of fermentation (2.37 x 107 CFU/mL) to 1.15 x 108 CFU/mL fermentation 4 days but decreased to 1.01 x 105 CFU/mL at the end of fermentation (6 days). The pH decreased from 6.43 ± 0.02 to 3.07 ± 0.002, and TTA increased from 0.31 ± 0.010% to 0.53 ± 0.008% at the end of fermentation (6 days). Organoleptic test results showed that fermentation time affected the preference level for color, taste, aroma, and texture. The highest preference level of the four aspects was the product with a fermentation time of 4 days with a preference level in the very like category. The results of this study indicate that the optimal time of gembili pickle fermentation is 4 days based on the total amount of LAB (> 106 CFU/mL), TTA (> 0.20%), pH (3.4-4.3) has met SNI criteria and also shows the highest preference level in color, taste, aroma, and texture. Gembili pickles can be recommended to be developed as a safe synbiotic product.